GERAKAN BERSIH PANTAI SEBAGAI UPAYA PENANGGULANGAN SAMPAH DI PANTAI KETAM DESA PONGKAR - Tisrin Maulina Dewi; Fadli Surahman; Rahmat Sanusi; Karunia Yulinda Khairiyah (Jurnal Pengabdian Ibnu Sina, 2022)
The purpose of this service activity is to provide awareness of environmental cleanliness and invite the community and tourists to maintain the cleanliness of the crab beach in Pongkar Village. The method used in this service is the observation and participation method with three stages of activities for the participants, namely before the activity, the implementation of the activity and after the activity. This service activity was carried out at Ketam Beach, Pongkar Tanjung Balai Karimun Village, which was attended by 62 people consisting of lecturers, students, the surrounding community and tourists. This beach clean-up activity can be carried out smoothly in accordance with the planned activities. This activity can develop the mindset of the community and increase their awareness in preventing environmental pollution which can later make the beach clean, beautiful and comfortable and can increase the visiting power of tourists to the beach.